STUDY ON THE CHANGES IN CHARACTERISTICS OF HIGHLY EXPANSIVE SOIL DUE TO ADDITION OF EGGSHELL POWDER - Teguh Padantha, Gerry
Infrastructure development around the world, particularly in Indonesia, faces various challenges. One of the problems encountered is the condition of expansive soils. Expansive soils have high strength in dry conditions, but their strength decreases when the moisture content increases. Additionally, as the name suggests, this soil expands with an increase in moisture content. The properties of expansive soil result in various potential problems in the surrounding areas, such as landslides and cracks due to soil expansion. This damage commonly occurs in lightweight structures such as houses or roads. Therefore, a solution is needed to prevent damage caused by the expansive nature of the soil. The commonly known method for improving expansive soil is the use of chemical stabilisators such as lime and cement. However, these materials are known to produce massive carbon emissions during mining, processing, and drying. These materials are not sustainable for continuous application. Thus, this research proposes an alternative stabilisator in the form of eggshell powder. Egg shells are proposed as an alternative stabilisator because they contain high levels of calcium carbonate, up to around 90%. Egg shells are a very common waste found in various industries, especially in the food and egg hatching industries, where eggshells accumulate as by-products in large quantities. This study will evaluate the changes in the properties of highly expansive soil with the addition of eggshell powder taken from two locations, Cirebon and Cipamingkis, Bogor. Changes in soil index properties, changes in methylene blue values, swelling potential and pressure, as well as unconfined compressive strength will be reviewed in this study. Additionally, the study will also examine the mineral content of the soil through X-Ray Diffraction tests, the calcium carbonate content and organic carbon in the eggshell powder, and changes in soil structure before and after treatment using an electron microscope. Mineralogical studies with X-Ray Diffraction showed a high quantity of muscovite in both soil samples. The Cirebon sample contained 93%, and the Cipamingkis sample contained 59%. Muscovite belongs to the mica family, which is less expansive and has low activity. However, muscovite is a polymorph of illite and montmorillonite, so the X-Ray Diffraction test cannot distinguish these three types of minerals. Special preparation is needed to separate the quantities of these three minerals in the testing process. Compaction tests on highly expansive soil produced an odd-shaped curve, consistent with the research by Lee and Suedkamp on soils with high liquid limit values. Therefore, this study did not obtain an optimum dry weight value for the soil due to the shape of the curve. The tests on compacted samples were conducted at an estimated optimum degree of saturation. The results showed that eggshell powder could reduce the expansive properties of the soil and increase its compressive strength, although not significantly. The swelling potential could decrease by around 20% from the initial value, and the compressive strength could increase to 324 kPa from 182 kPa in the Cirebon sample and to 275 kPa from 211 kPa in the Cipamingkis sample. The liquid limit and methylene blue values decreased with the increase in the quantity of the eggshell powder. The changes in properties were less significant due to the organic content in the eggshells, which reduced the effectiveness of the stabilisator.